Intake, digestibility of nutrients, milk production and composition in dairy cows fed on diets containing cashew nut shell liquid - Coutinho, Diogo Antignani (2014)
The study evaluated the effects of supplementing cashew nut shell liquid (CNSL) in the diet of lactating dairy cows on the intake, nutrient digestibility, milk yield and composition, and fatty acids composition of milk fat. Four Holsteincows (600±43 kg) were used in a 4 x 4 Latin square design with 21 days experimental periods. Experimental treatments consisted of CNSL inclusion in a total mixed ration (dry matter basis), as follows: 1) CNSL 0% (control, CON), 2) CNSL 0.012% (0.012), 3) CNSL 0.024% (0.024) and 4) CNSL 0.036% (0.036). Dry matter and nutrients intake, apparent digestibility of nutrients, fat corrected milk yield and milk composition were not affected (p > 0.05) by the inclusion of CNSL in the ration. CNSL linearly decreased the C6:0 concentration (p < 0.02), produced a quadratic response on C13:1n-5 concentration (p < 0.03) and a linear increase on C16:1n-7 concentration (p < 0.04). Results show that an intake of up to 7 gcow-1day-1 (0.036%) of CNSL may alter the milk fatty acid composition but does not influence intake, nutrient digestibility and milk yield.